Enhancing proactive vulnerability management integrating DevSecOps - Driss Alaoui Soulimani; Kadatska, O.; Shaimae Mishish (ХНУРЕ, 2025)
The need for robust security throughout the software development life cycle has grown with the rise in complex software ecosystems. This paper discusses the adoption of DevSecOps practices into Continuous Integration/Continuous Deployment pipelines to achieve proactive vulnerability detection and mitigation. Embedding security at every step of the SDLC, therefore, helps in minimizing risks, improving operational efficiency, and streamlining secure software delivery.
Keywords: DevSecOps